Changes in student learning styles over the course of postgraduate taught programmes and the impact of learning styles on achievement in various assessment modes - Phalkey, R.; Pritchard, Catherine; Myles, P. (2015)
Background: The impact of students preferred learning styles on their performance has been investigated in medical and nursing education but little has been done for students enrolling on postgraduate taught programmes in Public Health and Epidemiology. Summary of Work: We use the 40 item Honey and Mumford (1986) learning styles questionnaire that identifies four learning styles (Activist, Theorist, Reflector and Pragmatist) and administered it at the start (Oct 2014) and end of the course (May 2015). We plan a classroom discussion (May 2015) to understand whether and how students used this information in the course of their studies. On completion of the programme associations between learning styles and assessment scores across the course will be analysed. Summary of Results: Twenty of 27 enrolled students (12 Females) participated (response rate 74%). Half of them have acquired their previous education in Asia (1) or Africa (9) indicating different learning experiences. Students had average 6.7 years of work experience. Preliminary results from round one indicate that none of them were Activists, seven each were Reflectors and Theorists. Five of them were Reflectors and Theorists equally and only 3 showed Pragmatist as their dominant learning style. Discussion and Conclusions: Five (25%) showed more than one learning style. We expect the learning styles to evolve over the course and to find associations between individual learning styles and grades.